2012
DOI: 10.1179/2047773212y.0000000026
|View full text |Cite
|
Sign up to set email alerts
|

Edema surrounding calcified intracranial cysticerci: clinical manifestations, natural history, and treatment

Abstract: Calcified granulomas are the most common radiological finding in neurocysticercosis (10-20% of endemic populations). A small proportion serves as foci of seizure activity, which results in large numbers of persons with epilepsy. Calcified granulomas are not all the same. Some demonstrate blood-brain barrier dysfunction (magnetic resonance imaging enhancement) most likely due to the presence of inflammation, visualizable scolices, and/or gliosis. About half the patients with a recent history of seizures, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 49 publications
2
54
0
Order By: Relevance
“…Many studies have shown an association between the formation of calcified lesions and seizures,1, 2, 6, 33, 34 both of which may be more likely in subjects with a strong inflammatory response. Although the process by which calcifications form is not completely understood, a breakdown in the blood–brain barrier due to inflammation could allow calcium from the bloodstream to be deposited into the brain parenchyma 35, 36…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown an association between the formation of calcified lesions and seizures,1, 2, 6, 33, 34 both of which may be more likely in subjects with a strong inflammatory response. Although the process by which calcifications form is not completely understood, a breakdown in the blood–brain barrier due to inflammation could allow calcium from the bloodstream to be deposited into the brain parenchyma 35, 36…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammation as a contributing factor to seizures in subjects with calcified lesions has not been well studied, as these lesions have traditionally been thought to be immunologically inert. However, recent studies have provided evidence that calcifications may experience periodic remodeling that can expose parasite antigen and thus provoke a host immune response 1, 35, 37. Perilesional edema has been seen surrounding calcified lesions in symptomatic NCC patients,1, 2, 6 and PET scans evaluating this perilesional edema showed increased markers of neuroinflammation 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate calcifications are important foci of seizure activation. 3,4 The presence of enhancement around a subset of calcifications [5][6][7][8][9] the episodic occurrence of perilesional edema and seizure activity localized to some calcifications, 3,4,10 and the presence of significant inflammation in two excised lesions 11 (Nash and others, in preparation), strongly suggest the continued presence of inflammation associated with a subset of calcifications. This hypothesis implies that immune responses are periodically induced, perhaps by intermittent antigen release 10 or after episodic loss of suppressive immune inhibition, or some combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…The most favored hypothesis is that perilesional edema is caused by inflammation, perhaps as a result of intermittent release and/or recognition of enmeshed parasite antigen. 13 However, others hypothesize perilesional edema is a result of seizure activity or release of ionic calcium. 13 This is an important distinction, as therapies could differ, with immunosuppressive medications or antiepileptic drugs alone, respectively.…”
mentioning
confidence: 99%